Kingdom of the blind [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery., 2018)
When a peculiar letter arrives inviting Armand Gamache to an abandoned farmhouse, the former head of the Sûreté du Québec discovers that a complete stranger has named him one of the executors of her will. Still on suspension, and frankly curious, Gamache accepts and soon learns that the other two executors are Myrna Landers, the bookseller from Three Pines, and a young builder. None of them had ever met the elderly woman. The will is so odd and includes bequests that are so wildly unlikely that Gamache and the others suspect the woman must have been delusional. But what if, Gamache begins to ask himself, she was perfectly sane? When a body is found, the terms of the bizarre will suddenly seem less peculiar and far more menacing.